(untitled) (Academia Journal of Medicine, 2024)
This clinical trial evaluates the impact of audio and audiovisual distraction techniques on reducing anxiety in pediatric patients undergoing pit and fissure sealant application. A total of 60 children aged 6-12 requiring sealant application were randomly assigned into three groups: Control (no distraction), Audio distraction (listening to music), and Audiovisual distraction (watching cartoons). Anxiety levels were measured using the Venhem Anxiety Rating Scale (VARS) before and after the procedure. The study found a significant reduction in anxiety levels in the audio and audiovisual distractiongroups compared to the control group. Specifically, theaudiovisual group showed the greatest reduction in VARSscores, followed by the audio group.